(مشروعية الاستثمار في المشاريع التعلمية وضوابط الكسب والإنفاق المالي (دراسة في الاقتصاد الإسلامي The Legality of Investing in Educational Programs, as well as Financial Gain and Expenditure Limits (Study in Islamic Economics) - Ebrahim Abdul Jabbār Al Shāmirī, Hakim (International Journal of Al-Turath In Islamic Wealth and Finance, 2022)
تعتبر المؤسسات العلمية والمشاريع التعليمية من أهم المصادر في الاقتصاد الإسلامي، لكسب المال في العصر الحاضر، وأكثر المشاريع انتشاراً في المعمورة، فالشركات الكبرى تستثمر في بناء الجامعات وتشييد المعاهد، وتأسيس المدارس، وطبع المصاحف، ونشر الكتب العلمية، والمجلات المحُكّمة، والنشرات الثقافية، والمراكز التوعوية، وتقوم بتسويقها والعمل على نشرها وشهرتها بطرق ووسائل شرعية وغير شرعية، رغبة في الأرباح الخيالية، وطمعاً في الأموال التي تتحقق بدرجة متسارعة. ونحن نهدف من هذا البحث إلى إبراز الجانب الشرعي من الأموال المكتسبة من هذه المؤسسات، ومشروعية الإنفاق عليها والاستثمار فيها، ووضع ضوابطا وشروطا ومعاييرا تقنن مقدار المال المكتسب. كما نهدف إلى بيان التجاوزات التي قد تحدث من بعض المؤسسات العلمية في التدليس الدعائي والتلاعب الأكاديمي والتعليمي، وبيان حكم الوسائل والدعايات المستخدمة في الترويج للمؤسسات التعليمية لجلب الطلاب، وحكم الإفراط في الأرباح المالية التي يظهر عليها الجشع، وبعدها عن المهنية العلمية والأخلاق والقيم النبيلة. وتبرز أهمية البحث من خلال أهمية المحاور العلمية والمعرفية، ومكانتها في التشريع الإسلامي، واعتمد الباحث على مناهج عدة لتحقيق الأهداف، أبرزها الاستقراء والتحليل والاستنتاج. وقد توصل الباحث إلى مشروعية الكسب المالي من خلال الاستثمار في المشاريع التعلمية، والإنفاق عليها، بضوابط شرعية وقيم إسلامية ثابتة. Abstract Scientific institutions and educational projects are among the most important sources of income in the Islamic economy today, as well as among the most widespread projects worldwide. Major corporations invest in the construction of universities, institutes, and schools, as well as the printing of the Qur’an, the publication of scientific books, refereed journals, cultural publications, and awareness centers, marketing it and working on its dissemination and fame. The aim of this research is to highlight the legal aspects of the money earned from these institutions, as well as the legality of spending and investing in them, and to set controls, conditions, and criteria that regulate the amount of money earned. It also aims to discuss the abuses that may occur from some scientific institutions in terms of propaganda fraud and academic and educational manipulation, as well as to clarify the rule of the means and propaganda used in promoting educational institutions in order to attract students, as well as the rule of excessive financial profits on which greed and its scientific professionalism, morals, and noble values appear. The importance of scientific and cognitive axes, as well as their place in Islamic law, underline the significance of the study, and the researcher used a variety of methods to reach his objectives, including induction, analysis, and conclusion. According to Shariah controls and fixed Islamic values, the researcher experts to establish the validity of financial benefit by investing in and spending on educational programs.